Phylogenetic relationships among four new complete mitogenome sequences of Pelophylax (Amphibia: Anura) from the Balkans and Cyprus. (2nd September 2016) - Hofman, Sebastian; Pabijan, Maciej; Osikowski, Artur; Litvinchuk, Spartak N.; Szymura, Jacek M.
Abstract: We present the full-length mitogenome sequences of four European water frog species: Pelophylax cypriensis, P. epeiroticus, P. kurtmuelleri and P. shqipericus . The mtDNA size varied from 17, 363 to 17, 895 bp, and its organization with the LPTF tRNA gene cluster preceding the 12 S rRNA gene displayed the typical Neobatrachian arrangement. Maximum likelihood and Bayesian inference revealed a well-resolved mtDNA phylogeny of seven European Pelophylax species. The uncorrected p -distance for among Pelophylax mitogenomes was 9.6 (range 0.01–0.13). Most divergent was the P. shqipericus mitogenome, clustering with the " P. lessonae " group, in contrast to the other three new Pelophylax mitogenomes related to the " P. bedriagae/ridibundus " lineage. The new mitogenomes resolve ambiguities of the phylogenetic placement of P. cretensis and P. epeiroticus .